A Comparison of Second-Order Calibration Methods Applied to Excitation-Emission Matrix Fluorescence Data. (19th November 2014) - Chen, Hui; Lin, Zan; Wu, Tong; Tan, Chao
Abstract : Due to the variety of second-order data being generated by modern instruments and various mathematical algorithms being available for analysis purposes, second-order calibration is gaining widespread acceptance by analytical community. It has the so-called second-order advantage; that is, it enables concentration and spectral profiles of sample components to be extracted even in the presence of unexpected interferences. A comprehensive performance comparison of alternating trilinear decomposition (ATLD) and its two variants, that is, alternating penalty trilinear decomposition (APTLD) and self-weighted trilinear decomposition (SWATLD), was presented in this paper. The experiment was based on the simultaneous determination of three dihydroxybenzenes, that is, catechol, hydroquinone, and resorcinol, by excitation-emission matrix fluorescence (EEMF) spectroscopy. Two special measures, that is, the consistency (COS) between the resolved and actual profiles and the mean of recovery, were used for evaluation. The optimal result was obtained by the APTLD model with five components. No perceptible difference on the speed of convergence was found. It indicates that EEMF linked with the APTLD algorithm can serve as a potential tool of quantifying dihydroxybenzenes simultaneously in environmental samples.